Effects of Finger Counting on Numerical Development – The Opposing Views of Neurocognition and Mathematics Education - Moeller, Korbinian; Martignon, Laura; Wessolowski, Silvia; Engel, Joachim; Nuerk, Hans-Christoph (Frontiers in Psychology, 2011)
Usually children learn the basic principles of number and arithmetic by the help of finger-based representations. However, whether the reliance on finger-based representations is only beneficial or whether it may even become detrimental is the subject of an ongoing debate between neuro-cognitive and mathematics education researchers. From the neuro-cognitive perspective finger counting provides multi-sensory input conveying both cardinal and ordinal aspects of numbers. Recent data indicate that children with good finger-based numerical representations show better arithmetic skills and that training finger gnosis enhances mathematical skills. From this neuro-cognitive researchers conclude that elaborate finger-based numerical representations are beneficial for later numerical development. However, mathematics education research recommends fostering mental numerical representations so as to induce children to abandon finger-counting. More precisely mathematics education recommends moving from finger counting to concrete structured representations and then, finally, to mental representations of numbers. Taken together, there is obviously an important debate between the neuro-cognitve and mathematics education research concerning the benefits or detriments of finger-based strategies for numerical development. In the present review, the rationale of both lines of evidence will be presented and discussed.